2006
DOI: 10.1080/00420980600838606
|View full text |Cite
|
Sign up to set email alerts
|

Problem or Opportunity? Asylum Seekers, Refugees, Employment and Social Exclusion in Deprived Urban Areas

Abstract: The UK has become a leading proponent of European restrictionalism and has focused its efforts on developing policy that excludes asylum seekers from mainstream society. Dispersal policy has focused upon sending asylum seekers to excluded urban areas where there is an excess of available housing. This paper discusses the potential impacts of this approach on the economic prosperity and social cohesion of UK dispersal areas and focuses specifically on new migrants who arrived under the NASS dispersal programme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 27 publications
5
135
0
Order By: Relevance
“…Working towards building their professional skills is if fact recognised as crucial for the effective integration of refugees and it has a positive effect on their wellbeing (e.g. Beiser and Hou, 2001;Bloch, 2002;Phillimore and Goodson, 2006). This is line with Taylor et a.l' s view.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Working towards building their professional skills is if fact recognised as crucial for the effective integration of refugees and it has a positive effect on their wellbeing (e.g. Beiser and Hou, 2001;Bloch, 2002;Phillimore and Goodson, 2006). This is line with Taylor et a.l' s view.…”
supporting
confidence: 74%
“…This does not only impact on them financially, but also on their self-esteem and their mental health in general (Colic-Peisker and Tilbury 2003). This applies particularly to those who are highly qualified, as their skills and talents are often not encouraged to flourish in the new country, and in order to re-enter their profession, they need to follow longer and not always successful routes (Colic-Peisker and Tilbury 2007;Morrice, 2009;Phillimore and Goodson 2006;Shiferaw and Hagos, 2002). Participants therefore suggested that they would like to receive specific training on employment skills.…”
mentioning
confidence: 99%
“…The Home Office (2005,2009) themselves acknowledged that employment and housing were the two main social policy areas that were fundamental to integration. At the same time, studies have indicated that the lack of stable housing and employment continues to facilitate against refugee integration (Phillimore and Goodson, 2006). The New Labour government's 2005 report (Causes of Ethnic Minority Homelessness, Office of the Deputy Prime Minister) found that eviction from state-provided accommodation was one of the main causes of refugee homelessness.…”
Section: Integration Policy and Practicementioning
confidence: 99%
“…Access to appropriate housing and employment has long been viewed as fundamental to refugee integration (see Bloch, 2002;Phillimore and Goodson, 2006), and indeed formed part of the focus of early work on race and housing (i.e. Rex and Moore, 1967).…”
Section: Integration Policy and Practicementioning
confidence: 99%
“…This suggests that government policies have had a detrimental impact on the ability of asylum seekers who arrived from 2007 to access employment. Integration can be understood as a two way process where both the host country as well as refugees have responsibilities (Phillimore & Goodson 2006;Strang & Ager 2010). This means that governments need to enact policies to facilitate rather than impede the ability of people from a refugee background to resettle in the host country, including the provision of services and supports that enable access to employment (Correa-Velez, Barnett and Gifford 2015; Da Lomba 2010).…”
Section: What Can We Conclude?mentioning
confidence: 99%